Discovery of Shared Latent Nonlinear Effective Connectivity for EEG-Based Depression Detection - Yuan, Wenjie; Zhang, Xiaowei; Zhang, Xuejuan; Wang, Shuangyan; Wang, Tianzhi; Zhang, Tong; Zhao, Qinglin; Hu, Bin (IEEE transaction on neural networks and learning systems, 2025)
Granger causality (GC) effective connectivity (EC) calculated from electroencephalogram (EEG) signals has been widely used in mental disorder detection. However, the existing methods only take into account linear dynamics or nonlinear dynamics within a single sample, ignoring the nonlinear dynamics shared by the same class of subjects. In this article, a model combining graph neural networks (GNNs) and variational autoencoders (VAEs) is proposed to construct shared latent nonlinear EC from raw EEG signals for depression detection. Several convolution modules and fully connected layers are used in the graph encoding network to learn the embeddings of the connectivity connected by every two EEG channels. In the graph decoding network, a class-specific Gaussian mixture model (GMM) is introduced in the VAEs to model shared dynamics in EC of the same class of subjects, and the shared dynamics combine the encoded embeddings of the EC and the past time series to restore raw EEG signals. Through a node-to-edge encoding process and an edge-to-node decoding process, the shared latent nonlinear EC in EEG signals can ultimately be learned by gradually optimizing the model's loss function. The performance of the proposed method is verified on several open-accessed datasets. The excellent results prove that the proposed neural networks can learn more generalized nonlinear EC representations, and shared latent dynamics discovery can also help to identify depression better. The code is available at https://github.com/william-yuan2012/DSLNEC-tscausality .